Improved cryogenic interlaminar shear strength of glass fabric/epoxy composites by graphene oxide. (May 2015) - Shen, Xiao-Jun; Meng, Ling-Xuan; Yan, Zhi-Yong; Sun, Cheng-Jun; Ji, Yan-Hong; Xiao, Hong-Mei; Fu, Shao-Yun
Abstract: The cryogenic interlaminar shear strength (ILSS) at cryogenic temperature (77 K) of glass fabric (GF)/epoxy composites is investigated as a function of the graphene oxide (GO) weight fraction from 0.05 to 0.50 wt% relative to epoxy. For the purpose of comparison, the ILSS of the GF/epoxy composites is also examined at room temperature (RT, 298 K). The results show that the cryogenic ILSS is greatly improved by about 32.1% and the RT ILSS is enhanced by about 32.7% by the GO addition at an appropriate content of 0.3 wt% relative to epoxy. In addition, the ILSS of the composite at 77 K is much higher than that at RT due to the relatively strong interfacial GF/epoxy adhesion at 77 K compared to the RT case.